Estrategias metodológicas para incorporar la práctica deportiva como recursos didácticos y fortalecer la inteligencia kinestésica en los alumnos del séptimo grado de educación básica en el área de Cultura Física de la escuela Dr. Camilo Gallegos Domínguez de la ciudadela Jaime Roldos Aguilera del cantón Machala periodo 2013 - 2014. - Cuero Cabeza, Danny (2015)
This research thesis entitled Methodological strategies for incorporating SPORT PRACTICE AS EDUCATIONAL RESOURCES AND STRENGTHEN kinesthetic intelligence in seventh graders BASIC EDUCATION IN THE AREA OF PHYSICAL CULTURE SCHOOL DR. CAMILO GALLEGOS DOMÍNGUEZ CITADEL CANTON Jaime Roldós Aguilera MACHALA. PERIOD 2013 - 2014 is divided into five chapters where in chapter one problematization, research objectives, and hypotheses of how to incorporate sport as a teaching resource to strengthen kinesthetic intelligence in students were, in chapter two corresponds to the conceptual theoretical framework, where we investigate the methodological strategies that are used as teaching resources and materials specific area of physical education and everything about the kinesthetic intelligence, contextual under all that relates to the institution object of our study, and legal administrative framework based on human rights to education, sports law physical education and recreation, chapter three comprise the methodological aspects, research methods and data analysis, focus thereof, the universe and shows. The results of the research presented in chapter four, and their respective hypothesis testing, as well as the conclusions and recommendations to finally develop the proposed intervention, where a series of games are presented, the goal is to propose a guide games driving to guide teachers in the area of Physical Education to promote and encourage methodological development kinesthetic and coordinative skills in children in the seventh year basic education strategies.